2011
DOI: 10.1007/s11239-011-0562-0
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation in the management of venous thromboembolism in the cancer patient

Abstract: Cancer is associated with a four to sevenfold increased risk of venous thromboembolism (VTE). This risk is influenced by the site and extent of cancer and its treatment. Despite its availability, effective VTE prophylaxis is used in less than 50% of oncology patients. Pharmacologic VTE prophylaxis should be administered to all hospitalized medical and surgical oncology patients for the duration of their hospitalization or up to 10-14 days, whichever is longer. Extended duration (up to 4 weeks post-operation) V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 86 publications
(96 reference statements)
0
12
0
Order By: Relevance
“…The risk of VTE is 4 to 6 times higher in patients with cancer (Heit et al, 2000;Streiff, 2011). Previous DVT, type of cancer, stage of cancer (localized vs. distant metastasis), time of diagnosis (greatest within the first 3 months), surgery, RT (pelvic radiation relative risk 2.0), and chemotherapy/biological therapy/antiangiogenesis/other agents are factors that affect the risk of VTE development (Adess et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The risk of VTE is 4 to 6 times higher in patients with cancer (Heit et al, 2000;Streiff, 2011). Previous DVT, type of cancer, stage of cancer (localized vs. distant metastasis), time of diagnosis (greatest within the first 3 months), surgery, RT (pelvic radiation relative risk 2.0), and chemotherapy/biological therapy/antiangiogenesis/other agents are factors that affect the risk of VTE development (Adess et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…41 In addition, it has been shown that although 82% of patients receive in-hospital thromboprophylaxis, only 31% receive it after discharge. 36,42 In our study, all patients received some sort of in-hospital thromboprophylaxis (sequential compression devices þ chemical thromboprophylaxis or sequential compression devices þ early aggressive ambulation for those admitted to the hospital floor), with the majority receiving the former. At this time, postdischarge extended thromboprophylaxis is not used routinely at our institution.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, patients with continuous anticoagulation therapy were not eligible for study inclusion. The median time between a previous VTE event and study inclusion was 5 years (25th-75th percentile: [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. We recruited patients with newly diagnosed cancer and those with progressive disease after complete or partial remission.…”
Section: Discussionmentioning
confidence: 99%